Case report: Abrocitinib: a potential therapeutic option for lichen amyloidosis associated with atopic dermatitis - Zhang, Yizhen; Huang, Dawei; Gao, Yunlu (Frontiers in Immunology, 2024)
Lichen amyloidosis (LA) is a predominant type of primary cutaneous amyloidosis that is characterized by persistent and intense skin itching. Although multiple therapeutics strategies are available for its treatment, there is no standard treatment so far. Abrocitinib, an oral small-molecule Janus kinase 1 inhibitor, has been authorized for the treatment of severe atopic dermatitis (AD) and can also provide rapid relief from pruritus. Here, we discuss the case of a 32-year-old man who was diagnosed with LA with severe AD based on the presence of multiple, discrete, and hyperpigmented papules and pruritic, erythematous macules with lichenification of the limbs, trunk, and buttocks. Given the inefficacy of conventional therapy, abrocitinib treatment was recommended in this patient. After 1 month of treatment, the patient’s Eczema Area And Severity Index score decreased significantly from 48 to 15 points, accompanied by a notable reduction in pruritus symptoms. Furthermore, significant improvements were observed in the thickness and pigmentation of the hyperkeratotic papules. Thus, abrocitinib exhibited excellent effectiveness and safety in the treatment of severe AD with LA and warrants further investigation for its potential therapeutic benefits.